2012
DOI: 10.1111/jocn.12022
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of undergraduate nursing students towards mental health nursing: a systematic review

Abstract: Many nursing students regard mental health nursing as the least preferred career option. Education, via classroom teaching and clinical placements, seems to engender more positive attitudes towards mental health nursing. There is no evidence, however, that changing student attitudes results in more graduates beginning careers in mental health nursing. REFERENCE TO CLINICAL PRACTICE: The constancy of negative attitudes to mental health nursing over time suggests the focus of research should shift. Clinicians ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
190
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(221 citation statements)
references
References 26 publications
14
190
3
8
Order By: Relevance
“…Previous reports suggest that students are concerned and anxious about entering the mental health setting (Farrell & Carr 1996;Fisher 2002). Evidence consistently show that for those seeking a career in nursing, mental health is one of the least preferred areas (Happell and Gaskin 2013). For this reason, the mental health profession need to find ways of overcoming this challenge to enable it to recruit well qualified enthusiastic people.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Previous reports suggest that students are concerned and anxious about entering the mental health setting (Farrell & Carr 1996;Fisher 2002). Evidence consistently show that for those seeking a career in nursing, mental health is one of the least preferred areas (Happell and Gaskin 2013). For this reason, the mental health profession need to find ways of overcoming this challenge to enable it to recruit well qualified enthusiastic people.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Um estudo realizado com ingressantes de um curso de graduação de enfermagem demonstrou que há grande resistência por parte dos alunos em relação ao aprendizado com o doente mental, mostrado por valores e sentimentos estigmatizantes, medo, receio, temor, dó, pena, preconceito e, também, o difícil processo de compreensão, aceitação e manejo (13) . Outro estudo concluiu que as consequências dessas atitudes de estigma e preconceito podem impactar na escolha da área profissional a ser seguida, demonstrando que a saúde mental e psiquiatria possuem menor preferência da enfermagem para a potencial carreira profissional (14) . O maior contingente de grupos de pesquisa encontra-se nas Instituições de Ensino Públicas, já que possuem maior incentivo a programas de iniciação cientifica e pós-graduação.…”
Section: Resultsunclassified
“…Many studies showed that undergraduate nursing students have negative attitudes toward psychiatric and mental health nursing as a career, that make psychiatric nursing unpopular and not viewed as a favorable career choice (11) . Attitudes towards psychiatry and a career choice in psychiatry have many factors including demographics, social variables, personality and concern for the mentally ill (12&13) .…”
Section: Int J Adv Res 5(4) 844-852mentioning
confidence: 99%
“…This route didn't differ a cross socio economic classes and not affected by educational background, thus reflect the pervasiveness of this belief in the society. However, Happell & Gaskin (11) found that psychiatry component of the nursing course improved the attitude of the students toward discipline.…”
mentioning
confidence: 99%